دور الفايسبوك في نشر العنف الرياضي - باي، رياض, تماسيني، مصطفى (جامعة الوادي university of Eloued, 2020)
ملخص الدراسة: هدفنا من هذه الدراسة هو تبيان دور الفايسبوك في نشر العنف الرياضي، لاسيما أن هذا الموقع أصبح اليوم ذو تأثير كبير في تشكيل المواقف والآراء للأفراد والجماعات خاصة منهم الجماهير الرياضية، ومدى استخدامهم له والذي اثبت فعاليته في نشر وتوليد العنف الرياضي، فكان التساؤل الرئيسي للدراسة كالتالي: هل هناك علاقة بين موقع الفايسبوك والعنف في الملاعب؟ وتندرج تحته تساؤلات فرعية: 1- ماهي عادات وأنماط استخدام الفايسبوك لدى الجماهير؟ 2- هل للفاسبوك دور في نشر العنف الرياضي؟ 3- هل هناك علاقة بين ضعف التسيير والتنظيم داخل الملعب وانتشار ظاهرة العنف في ملاعب كرة القدم؟ وقد استخدمنا في دراستنا المنهج الوصفي وذلك لطبيعة الموضوع الذي يقتضيه هذا المنهج، واخترنا مجتمع بحث يتمثل في جماهير نادي التضامن السوفي لكرة القدم بالوادي، حيث كانت عينتنا عرضية، كذلك تم استخدام أداة الاستبيان لجمع البيانات وقد تضمن الاستبيان 30 سؤال في ثلاث محاور. Abstract: Our goal of this study was to show the role of Facebook in spreading sports violence, especially since this site has become today with a great influence in shaping the attitudes and opinions of individuals and groups, especially the sports fans, and the extent of their use of it, which has proven its effectiveness in spreading and generating sports violence, where the main question was To study as follows: - Is there a relationship between Facebook and violence in the stadiums? And sub-questions fall under it: -1What are the habits and patterns of using Facebook among the masses? -2 Does Facebook have a role in spreading sports violence? -3Is there a relationship between poor management and organization on the stadium and the spread of violence in football stadiums? We used in our study the descriptive approach due to the nature of the subject required by this approach, and we chose a research community represented by the masses of the Soviet Solidarity Football Club in the valley, where our sample was occasional, and the questionnaire tool was used to collect data and the questionnaire included 30 questions in three axes.
دراسة ميدانية على جماهير نادي التضامن السوفي لكرة القدم بالوادي
مذكرة ماستر في علم الإجتماع تخصص علم إجتماع الإتصال
Keywords: مواقع التواصل الاجتماعي، الفايسبوك، العنف الرياضي; Sites de réseautage social, Facebook, violence sportive; Social networking sites, Facebook, sports violence